Biomarker counseling, disclosure of diagnosis and follow‐up in patients with mild cognitive impairment: A European Alzheimer's disease consortium survey. (16th September 2020) - Frederiksen, Kristian S.; Nielsen, Thomas R.; Appollonio, Ildebrando; Andersen, Birgitte Bo; Riverol, Mario; Boada, Mercè; Ceccaldi, Mathieu; Dubois, Bruno; Engelborghs, Sebastiaan; Frölich, Lutz; Hausner, Lucrezia; Gabelle, Audrey; et al.
Abstract: Objectives: Mild cognitive impairment (MCI) is associated with an increased risk of further cognitive decline, partly depending on demographics and biomarker status. The aim of the present study was to survey the clinical practices of physicians in terms of biomarker counseling, management, and follow‐up in European expert centers diagnosing patients with MCI. Methods: An online email survey was distributed to physicians affiliated with European Alzheimer's disease Consortium centers (Northern Europe: 10 centers; Eastern and Central Europe: 9 centers; and Southern Europe: 15 centers) with questions on attitudes toward biomarkers and biomarker counseling in MCI and dementia. This included postbiomarker counseling and the process of diagnostic disclosure of MCI, as well as treatment and follow‐up in MCI. Results: The response rate for the survey was 80.9% (34 of 42 centers) across 20 countries. A large majority of physicians had access to biomarkers and found them useful. Pre‐ and postbiomarker counseling varied across centers, as did practices for referral to support groups and advice on preventive strategies. Less than half reported discussing driving and advance care planning with patients with MCI. Conclusions: The variability in clinical practices across centers calls for better biomarker counseling and better training to improve communication skills. Future initiatives should address the importance of communicating preventive strategies and advance planning.